15 years of microbial biotechnology: the time has come to think big—and act soon. Issue 1 (21st December 2021) - de Lorenzo, Víctor
Summary: Our epoch is largely characterized by the growing realization and concern about the reality of climate change and environmental deterioration, the surge of global pandemics, the unacceptable inequalities between developed and underdeveloped countries and their unavoidable translation into messy immigration, overpopulation and food crises. While all of these issues have a fundamentally political core, they are not altogether removed from the fact that Earth is primarily a microbial planet and microorganisms are the key agents that make the biosphere (including ourselves) function as it does. It thus makes sense that we bring the microbial world—that is the environmental microbiome—to the necessary multi‐tiered conversation (hopefully followed by action) on how to avoid future threats and how to make our globe a habitable common house. Beyond discussion on governance, such a dialogue has technical and scientific aspects that only frontline microbial biotechnology can help to tackle. Fortunately, the field has witnessed the onset of new conceptual and material tools that were missing when the journal started. Abstract : Microbial Biotechnology enters a new period framed by the awareness of climate change and its consequences. Fortification of the environmental microbiome with a suite of agents with enhanced bioremediation activities (from monoclonal strains to self‐propagating DNA) will be paramount for reverting emissions to pre‐industrial levels.